'I felt a sense of panic, disorientation and frustration all at the same time': the important role of emotions in reflective practice. Issue 3 (4th May 2022) - Farrell, Thomas S. C.
ABSTRACT: For many novice teachers, their first year on the job can be a roller coaster experience of 'ups' and 'downs' as they transition from their teacher education programs to teaching in real classrooms. While to 'ups' are always good to experience, the 'downs' can be so traumatic that novice teachers can feel so stressed that their teaching is adversely impacted and burned out to the point that they consider resigning for the profession. For the most part, however, the language teaching profession has not addressed this aspect of a novice ESL (English as a second language) teacher well-being in terms of their personal and emotional investment as they transition from trainee to novice teacher in their first year. This paper attempts to shed light on the emotional experiences of three female novice ESL teachers in a university language school in Canada as they reflected during regular group discussions and journal writing during their first semester (12 weeks) as novice ESL teachers. The results reveal that the group discussions and journal writing provided a platform for the teachers to articulate their mostly negative emotions with three most frequently expressed: frustration, anger and boredom.